Autophagy in Alcoholic Liver Disease, Self-eating Triggered by Drinking - Wang, Lin (Clin Res Hepatol Gastroenterol, 2015)
Macroautophagy (autophagy) is an evolutionarily conserved mechanism. It is important for normal cellular function and also plays critical roles in the etiology and pathogenesis of a number of human diseases. In alcohol-induced liver disease, autophagy is a protective mechanism against the liver injury caused by alcohol. Autophagy is activated in acute ethanol treatment but could be suppressed in chronic and/or high dose treatment of alcohol. The selective removal of lipid droplets and/or damaged mitochondria is likely the major mode of autophagy in reducing liver injury. Understanding the dynamics of the autophagy process and the approach to modulate autophagy could help finding new ways to battle against alcohol-induced liver injury.